A study on construction industry: the capital structure of Malaysian firms / Amirah Hanim Mohammed Isa - Mohammed Isa, Amirah Hanim (Faculty of Business and Management, 2012)
Capital structure is a business term that describes the proportion of debts and equity used to finances the firm`s assets. According to this problem, this study was done, where the main purpose is to determine the correlation between leverage ratio, size of firms, profitability, firm`s growth and capital intensity. This study focus on construction industry. Three independent variables were developed which are size of firm, profitability, firm`s growth and capital intensity while the dependent variable is leverage ratio. Data collected and evidences are being processed by using the e-view software. The researcher also wants to test the hypothesis formulated earlier by using the regression models from the finding, we will know the four factors are same line with the theories of capital structure or not. For recommendation, the further study can be done by determined other attributes such as age, business risk and net debt tax shield. By testing this attributes, it can provided the construction firms to more concern about the capital structure especially in choice to used debt financing or equity financing in order to finance their assets.